Manajemen Sumber Daya Manusia dalam Pengembangan Profesionalitas Guru di MTs Plus Baitussalam Banyuwangi - Izzah, Nur Aqidatul; Fauzi, Imron (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
This study explores human resource management (HRM) in developing teacher professionalism at MTs Plus Baitussalam Banyuwangi, focusing on planning, implementation, and evaluation. Using a qualitative case study, data were collected through interviews, observation, and documentation, and analyzed with Miles and Huberman’s interactive model. Findings show that in the planning stage, school leaders conducted needs, job, and workload analysis, along with identifying teachers’ strengths and weaknesses to align with institutional goals. The implementation emphasized teacher recruitment based on pedagogical, professional, social, and personal competencies, followed by development programs such as MGMP, workshops, and training. Evaluation was conducted through regular meetings, teacher performance appraisals, and feedback sessions to address weaknesses and foster innovation. The study concludes that systematic and continuous HRM effectively strengthens teacher professionalism, competitiveness, and commitment, thus contributing to improving the quality of Islamic education. Penelitian ini mengkaji manajemen sumber daya manusia (SDM) dalam mengembangkan profesionalitas guru di MTs Plus Baitussalam Banyuwangi dengan fokus pada perencanaan, pelaksanaan, dan evaluasi. Menggunakan pendekatan kualitatif studi kasus, data diperoleh melalui wawancara, observasi, dan dokumentasi, lalu dianalisis dengan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa pada tahap perencanaan, kepala madrasah melakukan analisis kebutuhan, jabatan, dan beban kerja serta memetakan kelebihan dan kelemahan guru untuk mendukung visi misi lembaga. Pada tahap pelaksanaan, rekrutmen guru berlandaskan empat kompetensi utama—pedagogik, profesional, sosial, dan kepribadian—serta dilengkapi program pengembangan seperti MGMP, workshop, dan pelatihan. Evaluasi dilaksanakan melalui rapat rutin, penilaian kinerja guru (PKG), dan forum masukan terbuka guna memperbaiki kekurangan sekaligus menumbuhkan inovasi. Penelitian menyimpulkan bahwa manajemen SDM yang terarah dan berkelanjutan mampu meningkatkan profesionalitas, daya saing, serta komitmen guru dalam mendukung mutu pendidikan Islam.